Rancangan Kriteria Evaluasi Penerapan Eco-Design Pada Roof Garden - Sabila, Yola Rahma; Fatimah, Indung Sitti; Gunawan, Andi (http://arl-faperta.ipb.ac.id/, 2025)
The high density of cities encourages efforts to create ecological balance, one of which is through the implementation of roof gardens. Roof garden research began with the exploration of its benefits for energy management and currently still can be studied to find a more thorough criteria of applicable roof gardens. Following the growth of the sustainable movement, there is a high need to create design criteria on the basis of eco-design, incorporating environmental aspects to reduce environmental impacts. This concept has been integrated into green building practices through the use of ‘Greenship rating tools’, however, the criteria for roof gardens have not been comprehensively outlined. Therefore, this research aims to: 1) identify and determine the priority level of the criteria as the key to evaluate eco-design implementation in roof gardens; and 2) develop implementation strategies based on the significance of various alternative decisions from experts. This research was conducted by using Analytical Hierarchy Process (AHP) method through the assessment of selected experts. This research shows that, by hierarchy, the key criteria of eco-design in roof gardens based on significance are: water management (24,4%), vegetation (23,0%), roof garden physical aspects (13,2%), technology (11,5%), management aspect (11,5%), building physical aspect (11,1%), and user behavior (5,3%). The strategy to implement eco-design in roof gardens would be best implemented by several strategies involving: 1) development of a comprehensive roof design concept, 2) the use of environmentally friendly technology and materials; and 3) efficient resource management.